Peran Lingkungan Keluarga Terhadap Motivasi Belajar Siswa Sekolah Dasar - Yeni Nuraeni; Dini Indahyani; Irma Agustin; Siti Nurhidayah; Syafira Rizkyta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of family environment in motivating elementary school students to learn. Family education is the initial foundation in the formation of learning motivation that contributes greatly to students' academic success. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The results showed that a harmonious family environment, parental attention, and providing motivation consistently had a significant effect on increasing students' learning motivation. Factors such as managing study time, monitoring academic progress, and developing children's personalities are important aspects in supporting learning. We conclude that parents' active involvement in creating a conducive learning atmosphere and providing internal and external motivation can improve students' learning success. The findings are expected to enrich insights into the importance of the family's role in students' education.